Novel Role of Toll-Like Receptor 3 in Hepatitis C-Associated Glomerulonephritis - Wörnle, Markus (American Society for Investigative Pathology, 2006)
Hepatitis C virus (HCV) infection is frequently complicated by glomerulonephritis with immune complexes containing viral RNA. We examined the potential influence of Toll-like receptors (TLRs), specifically TLR3 recognition of viral dsRNA exemplified by polyriboinosinic:polyribocytidylic acid [poly(I:C) RNA]. Normal human kidney stained positive for TLR3 on mesangial cells (MCs), vascular smooth muscle cells, and collecting duct epithelium. Cultured MCs have low TLR3 mRNA levels with predominant intracellular protein localization, which was increased by tumor necrosis factor-α, interleukin (IL)-1β, interferon (IFN)-γ, and the TLR3 ligand poly(I:C) RNA. Poly(I:C) RNA stimulation of MCs increased mRNA and protein synthesis of IL-6, IL-1β, M-CSF, IL-8/CXCL8, RANTES/CCL5, MCP-1/CCL2, and ICAM-I; it also increased anti-proliferative and proapoptotic effects, the latter of which was decreased by inhibiting caspase-8. In microdissected glomeruli of normal and non-HCV membranoproliferative glomerulonephritis biopsies, TLR3 mRNA expression was low. In contrast TLR3 mRNA expression was significantly increased in hepatitis C-positive glomerulonephritis and was associated with enhanced mRNA for RANTES/CCL5 and MCP-1/CCL2. We hypothesize that immune complexes containing viral RNA activate mesangial TLR3 during HCV infection, thereby contributing to chemokine/cytokine release and effecting proliferation and apoptosis. Thus, TLR3 expression on renal cells, and especially MCs, may establish a link between viral infections and glomerular diseases.